2023
DOI: 10.1001/jama.2023.12739
|View full text |Cite
|
Sign up to set email alerts
|

Door-in-Door-out Times for Interhospital Transfer of Patients With Stroke

Abstract: ImportanceTreatments for time-sensitive acute stroke are not available at every hospital, often requiring interhospital transfer. Current guidelines recommend hospitals achieve a door-in-door-out time of no more than 120 minutes at the transferring emergency department (ED).ObjectiveTo evaluate door-in-door-out times for acute stroke transfers in the American Heart Association Get With The Guidelines-Stroke registry and to identify patient and hospital factors associated with door-in-door-out times.Design, Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In Reply We acknowledge the comments from Dr Hsu and colleagues and thank them for their interest in our study. However, we believe the findings from our study are both important and meaningful despite the concerns regarding prespecified target benchmarks for door-in-door-out time and our approach to cohort assembly.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In Reply We acknowledge the comments from Dr Hsu and colleagues and thank them for their interest in our study. However, we believe the findings from our study are both important and meaningful despite the concerns regarding prespecified target benchmarks for door-in-door-out time and our approach to cohort assembly.…”
mentioning
confidence: 80%
“…Although it is accurate that the door-in-door-out recommendation of less than 120 minutes proposed by the Brain Attack Coalition and the Joint Commission is not currently reflected in formal guidelines, this benchmark nevertheless represents an important quality metric in the management of acute stroke. The aim of our study was not to determine the appropriate cut point for door-in-door-out times, although it is clear from our analysis that the median door-in-door-out time of 174 minutes from Get With the Guidelines (GWTG)–participating hospitals far exceeds this proposed target . Furthermore, our primary analysis and outcome included door-in-door-out as a continuous variable, in which we identified several important factors independently associated with door-in-door-out time, irrespective of a particular dichotomized cut point.…”
mentioning
confidence: 99%
“…To the Editor We have several concerns about the recent article that reported that median door-in-door-out time was longer than current recommendations for acute stroke transfer in the US.…”
mentioning
confidence: 99%
“…The 2-hour rule lacks universal consensus and has not been established as a guideline. Therefore, this study may require sensitivity analyses using various cutoffs to confirm the presence of factors contributing to extended door-in-door-out times. For example, when using a 120-minute threshold as a dichotomous end point, the authors observed an association between conducting magnetic resonance imaging (MRI) and extended door-in-door-out time .…”
mentioning
confidence: 99%
See 1 more Smart Citation